Strategic planning for Small Country National Agricultural Research Systems in the South Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Small Country National Agricultural Research Systems (NARS) face the same range of problems that confronts researchers in larger developing countries and yet have fewer resources to undertake the scope of research required. They therefore have to...